Neurogical deficit score dan gambaran hematologi tikus model strok iskemik dengan metode middle cerebral artery occlusion - Ika Satya Perdhana; Muhamad Evans Hardiansyah; Hera Maheshwari; Kusdiantoro Mohamad (ARSHI Veterinary Letters, 2025)
Stroke is a neurological disorder caused by impaired blood flow to specific regions of the brain, often resulting in paralysis and functional deficits in the affected area. Among its subtypes, ischemic stroke is the most prevalent in the general population. This study aimed to establish a rat model of ischemic stroke induced by middle cerebral artery occlusion (MCAO). Eight male Sprague-Dawley rats aged 8–10 weeks were randomly assigned to two groups: control and treatment group. In the treatment group, the middle cerebral artery was occluded for 45 min. Neurological assessment using the Bederson scale revealed a neurological deficit score (NDS) of 1, characterized by contralateral flexion after left-brain injury. Hematological analysis demonstrated significantly higher white blood cell (WBC) counts (p < 0.05), whereas red blood cell (RBC) counts, hemoglobin concentration, and hematocrit values were significantly lower (p < 0.05) than those in the control group. These findings indicate that the MCAO method with a 45-minute occlusion successfully induced a mild neurological deficit accompanied by distinct hematological alterations, thereby providing a reproducible animal model for ischemic stroke research.